Struktur Komunitas dan Tutupan Kanopi Mangrove Pada Kawasan SFV (Smart Fisheries Village) Pasaman Barat - Walqodra, Aldi Rizki; Purnama, Dewi; Anggoro, Ari; Adi, Rizky Anggoro (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Mangrove forests are tropical and subtropical coastal vegetation communities that can grow and develop in muddy coastal intertidal areas. This study aimed to identify and analyze the structure and canopy cover of mangrove ecosystems in SFV (Smart Fisheries Village). The research was conducted using a survey method. The observation station was determined by purposive sampling method. Data analysis was done using descriptive statistical methods. Mangroves in SFV (Smart Fisheries Village) West Pasaman are Avicennia marina, Rhizophora apiculata, Sonneratia alba, and Aegiceras corniculatum. The highest density of mangrove trees, saplings, and seedlings are 500 Ind/ha, 3866.67 Ind/ha, and 66666.67 Ind/ha with mangrove species Rhizophora apiculata. The highest frequency of tree category species with Rhizophora apiculata species is at stations 1, 2, 3 and Soneratia alba at stations 1 and 3. The highest frequency of seedling category species is Rhizophora apiculata at all three stations, Soneratia alba at station 3, and Avicennia marina at station 2. The highest frequency of seedling category species at all three stations is Rhizophora apiculata and Soneratia alba at station 3. The highest mangrove species cover is Rhizophora apiculata at stations 1 and 2 with a value of 68.04% (station 1), 69. 81%, (Station 2), and Soneratia alba 50, 35%, (Station 3) The index of important value (INP) of mangroves at the level of trees, saplings, and seedlings is highest in the species Rhizophora apiculata successively at all stations The value of diversity index (H') is categorized as low, while the dominance index is categorized as moderate. The percentage of mangrove canopy cover is classified as mild.